Comparison of epidemiological and clinical features between two chronological cohorts of patients with intracerebral hemorrhage. (February 2020) - Zou, Yongjie; Zhang, Chao; Ge, Hongfei; Li, Huanhuan; Fang, Xuanyu; Zhong, Jun; Guo, Peiwen; Feng, Hua; Hu, Rong
Highlights: We retrospective analysis clinical characteristics of 1598 patients with ICH. The incidence of ICH in younger patients increased in our institution. Hypertension, smoking, drinking were major risk factors of ICH. Pulmonary infection were increased, more strategies should be improved. Abstract: To investigate the differences in the epidemiological and clinical characteristics of patients with intracerebral hemorrhage (ICH) treated at our institution over the last few decades. Two chronological cohorts with ten-year-interval were established and epidemiological and clinical data were retrospectively collected from patients with ICH, and data were analyzed using SPSS 13.0. The time windows for the two cohorts were from January 1, 2010 to December 31, 2014 (2010–2014 cohort) and January 1, 2000 to December 31, 2004 (2000–2004 cohort). 1598 patients with ICH were enrolled: 360 patients in the 2000–2004 cohort and 1238 patients in the 2010–2014 cohort. ICH often occurred in patients aged from 45 to 75 years, without a sex bias, accounting for 69.6% of patients. Hypertension (60.7%) was still the main risk factors. Meanwhile, the risk factors of smoking (28.9%) and drinking (23.3%) were often present in male patients but not female patients (p ≤ 0.001). The incidence of pulmonary infection, the main complication during hospitalization, was 40.8% in the 2000–2004 cohort and 61.8% in the 2010–2014 cohort (p ≤ 0.001). Moreover, the incidence of gastrointestinal hemorrhage was 12.5% in the 2000–2004 cohort and 6.0% in the 2010–2014 cohort (p ≤ 0.001). The epidemiological and clinical features have changed over the past 10 years. The mortality was reduced but still high, as evidenced by the increased hospitalization rate of patients with ICH. Current preventions and therapeutic strategies for ICH are effective, but more strategies must be developed to improve the outcome of ICH and decrease the incidence of pulmonary infection.